A SECOND LANGUAGE ACQUISITION. PRACTICING THE METHOD OF VIRTUAL CROSS-CULTURAL INTERACTION: INNOVATION OR ROUTINE? - Žegunienė, Vaida; Kupriene, Laima (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The current situation in the global arena may be characterized as a rapidly changing process with new trends appearing. This situation is not a problem for the young generation which has many different names, such as the “Net Generation”, “Digital Natives”, “Y” and/or “X” Generation, etc. As a matter of fact, these modern names are closely associated withhigh consumption of virtual media, such as the Internet. A great majority of young individuals perceive their own existence mainly in the virtual space. Thus, themodern approachto communication demonstrated by the young generation cannot be refuted by any educationalinstitution or governmental body which are involved invarious processes of policy creation and regulation of modern societal norms. The educational system can be referred to as a priority in the entire world, because newly educated and trained specialists take an active part in the processesof economic, political, education, etc. development aiming to create a positive image of their country in the world. Multilingualism is part ofthe daily life due to the provided ability to communicate atan international level. New opportunities, such as travelling or jobsand studies abroad, expand people's horizons and demand new skills. A second language is amustin the contemporary world. Language acquisition is more efficient when innovations are integrated into the educational field. This article aims at revealingthe methods of practice ofvirtual cross-cultural interaction facilitating the acquisition and development of the foreign language communication skills. The conducted survey suggests thatvirtual cross-cultural interaction is an innovative routine acknowledged by every respondent, andallthe positive aspects are clearly and indisputably presented by the survey participants.